The Role of Family and School in Instilling Pancasila Values in Elementary School Children - Vino, Adelia; Andini, Trie Wahyu; Pramudya, Pramudya; Hayati, Auliya Aenul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study analyzes the role of families and schools in instilling Pancasila values among elementary school students. A quantitative descriptive approach was employed, using an online survey questionnaire administered to 5th and 6th grade students at SDN Payung 2. Three indicators were examined: the role of the family, the role of the school, and students' attitudes as behavioral expressions of Pancasila value internalization. Data were analyzed through percentage categorization with a 4-point Likert scale to determine the effectiveness of each educational environment. The findings show that the family's role is categorized as very strong (100%), the school's role as very strong (97%), and students' attitudes likewise at very strong (97%). No respondents expressed strong disagreement, with only 3–4% indicating disagreement — reflecting consistent character formation across indicators such as politeness, tolerance, mutual cooperation, and discipline. The study concludes that close collaboration between family and school is central to Pancasila-based character formation, producing students who are responsible, tolerant, and prepared to contribute as Indonesian citizens.